(untitled) (Research, Society and Development, 2021)
Currently, one of the greatest challenges for adhesive dentistry is to maintain the integrity of the hybrid layer in restorations. It is known that the complicating factor is related to the action of matrix metalloproteinase (MMP), which degrade unprotected collagen filaments. It is understood that chlorhexidine (CHX) behaves in an inhibitory manner on this enzyme, changing its structure and chelating the metal ions essential for its activation, which would break this degradation sequence. One of the aims of this study was to describe, based on the literature, the influence of the use of CHX prior to the application of the adhesive system on the conservation of the hybrid layer and, consequently, on the improvement of composite resin bonding. Another purpose is to verify, among the adhesive systems, if any elucidates better results after the application of CHX and to understand if, in the long term, this inhibition is maintained. This research was carried out as an integrative literature review, and is purely basic in nature. To this end, a search was conducted in the "PubMed-NCBI" database with the search terms: ((chlorhexidine) and (matrix metalloproteinase inhibitors)) or (mmp) and (adhesives) considering publications from the last 10 years. Given the data collected it is clear that this is still a subject that requires further and longer scientific evidence due to the heterogeneity of results between authors. However, no study has shown that the use of inhibitors is detrimental to the longevity of the restoration.